Sharia Bank Sharia Index - Sukmana, Dedy (Dinasti Publisher, 2025)
This paper discusses the concept of the Shariah Index or Shariah Compliance Index for Islamic banks. The purpose of this index is to evaluate the extent to which these banks comply with the principles and practices of Shariah law, which governs all financial transactions in Islamic banking. This index is essential to ensure that Islamic banks provide financial products and services that are in accordance with the ethical and religious guidelines set by Islam. This paper explores the creation, development, and significance of the Shariah Compliance Index, including its impact on the financial performance, customer trust, and overall credibility of Islamic banking institutions.